2022
DOI: 10.21577/0103-5053.20210167
|View full text |Cite
|
Sign up to set email alerts
|

Natural and Semisynthetic Triterpenes from Combretum leprosum Mart. with Antiplasmodial Activity

Abstract: Malaria is responsible for thousands of deaths each year. Currently, artemisinin combination therapy (ACT) is used as first-choice medication against the disease. However, the emergence of resistant strains prompts the search for alternative compounds. The present study aimed to investigate the antiplasmodial activities of natural triterpenes (compounds 1 and 2), and semisynthetic derivatives 1a, 1b, 1c, and 1d. Antiplasmodial assays were carried out using the SYBR Green technique, whereas cytotoxicity was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The results showed that natural triterpenes isolated from C. leprosum have antimalarial and antiplasmodial activity, which may represent an important tool in the development of drugs associated with the treatment of malaria (Passarini et al, 2022). In addition to the antimalarial application, Araújo et al (2021) associate the use of 3β, 6β, 16β-trihydroxylup-20(29)ene in the treatment against T. cruzi, being observed that the compound is well absorbed in the test organism and presents low toxicity, being able to be a candidate in the developed of new options for the treatment of Chagas disease.…”
Section: Biological and Pharmacological Activitiesmentioning
confidence: 99%
“…The results showed that natural triterpenes isolated from C. leprosum have antimalarial and antiplasmodial activity, which may represent an important tool in the development of drugs associated with the treatment of malaria (Passarini et al, 2022). In addition to the antimalarial application, Araújo et al (2021) associate the use of 3β, 6β, 16β-trihydroxylup-20(29)ene in the treatment against T. cruzi, being observed that the compound is well absorbed in the test organism and presents low toxicity, being able to be a candidate in the developed of new options for the treatment of Chagas disease.…”
Section: Biological and Pharmacological Activitiesmentioning
confidence: 99%